The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/ange.201403046
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Synthesis of 3,3′‐Diaryloxindoles as Triarylmethanes with a Chiral All‐Carbon Quaternary Center: Phase‐Transfer‐Catalyzed SNAr Reaction

Abstract: Catalytic asymmetric synthesis of unsymmetrical triarylmethanes with a chiral all‐carbon quaternary center was achieved by using a chiral bifunctional quaternary phosphonium bromide catalyst in the SNAr reaction of 3‐aryloxindoles under phase‐transfer conditions. The presence of a urea moiety in the chiral phase‐transfer catalyst was important for obtaining high enantioselectivity in this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 101 publications
(2 reference statements)
0
14
0
Order By: Relevance
“…In the past decades,a symmetric phase-transfer catalysis (PTC) has been recognized as ap owerful and versatile tool for the enantioselective synthesis of chiral compounds,a nd numerous quaternary ammonium salts [11] have been commonly employed in PTC.H owever,a symmetric PTC involving phosphonium salts as catalysts is still underdeveloped. [12,13] Thekey breakthroughs in this field were recently reported by the groups of Maruoka [14] and Ooi. [15] Later, Ma and coworkers introduced abinol-derived P-spiro-phosphonium salt and realized its use in asymmetric amination of benzofuranones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades,a symmetric phase-transfer catalysis (PTC) has been recognized as ap owerful and versatile tool for the enantioselective synthesis of chiral compounds,a nd numerous quaternary ammonium salts [11] have been commonly employed in PTC.H owever,a symmetric PTC involving phosphonium salts as catalysts is still underdeveloped. [12,13] Thekey breakthroughs in this field were recently reported by the groups of Maruoka [14] and Ooi. [15] Later, Ma and coworkers introduced abinol-derived P-spiro-phosphonium salt and realized its use in asymmetric amination of benzofuranones.…”
mentioning
confidence: 99%
“…TheO-TBDPS-l-Thr-d-tert-Leu-based phosphonium salt 4b turned out to be the best, affording the Darzens reaction product in 93 %y ield and with 72 % ee (entry 9). Subsequently,w e further optimized the reaction conditions with respect to the base (entries [10][11][12][13][14]. Among all the bases tested, it was found that 4.0 equivalents of K 3 PO 4 ·7 H 2 Op roved to be the best, and the ee value could be improved to 78 %( entry 14).…”
mentioning
confidence: 99%
“…[6] Thea symmetric variants of these acid-catalyzed aza-Darzens reactions were first reported by Wulff and co-workers [7] and further developed by Maruoka and co-workers, [8] and others, [9] particularly providing cis-o r/and trans-disubstituted aziridines in high yields with excellent stereoselectivities.However,less success has been achieved in direct construction of trisubstituted chiral aziridine scaffolds by this process,a nd only two examples were reported. [12,13] Thekey breakthroughs in this field were recently reported by the groups of Maruoka [14] and Ooi. [10a] Quite recently, Tr ost developed aZ n-ProPhenol catalyzed aza-Darzens reaction of chlorinated aromatic ketones with N-Boc aldimines,p roviding an ovel method for constructing trisubstituted chiral aziridine motifs.…”
mentioning
confidence: 99%
“…[16] More recently,t he groups of Zhao [17] and Lu [18] derived several phosphonium salt catalysts from amino acids and initially demonstrated their effectiveness in asymmetric conjugate additions and substitution reactions.N otably,s uch amino-acid-based phosphonium salts possess remarkably high tunability,but their utilization in asymmetric synthesis is rare to date.Aspart of our research interest in the development of asymmetric synthetic methods catalyzed by amino-acid-based organocatalysts, [19] we envisioned that employment of highly tunable bifunctional phosphonium salts may result in apractical asymmetric aza-Darzens cyclization protocol to construct densely tri-and tetrasubstituted aziridine cores (Scheme 2). Subsequently,w e further optimized the reaction conditions with respect to the base (entries [10][11][12][13][14]. Foro ur initial investigations,t he aza-Darzens reaction between the cyclic N-sulfonyl a-ketimino ester 5a and abromoacetophenone (6a)w as chosen as am odel reaction to evaluate catalytic effects of the candidate bifunctional phosphonium salts (Table 1), which were prepared in our laboratory by aP -alkylation reaction of our previously reported organophosphines [19] with the appropriate alkyl halides.P leasingly,a ll the phosphonium salts examined were effective in promoting this reaction, leading to the desired aziridine products in moderate to excellent yields with high diastereoselectivities.G enerally, l-valine-derived bifunctional phosphonium salts with either as ulfonamide, amide,thiourea, or dipeptide were found to be ineffective in asymmetric induction, affording the cyclization products with low ee values (entries [1][2][3][4][5].…”
mentioning
confidence: 99%
“…[2] As as ubset, 3,3'-diaryloxindoles represent an important class of molecules that bear an all-carbon quaternary center and exhibit potent biological activities. [4] However,this method was limited to the nitro-containing aryl fluorides.Given the challenges and the high value of the 3,3'diaryloxindoles,t he development of ag eneral and robust protocol for accessing this important structural motif would be highly desirable. [4] However,this method was limited to the nitro-containing aryl fluorides.Given the challenges and the high value of the 3,3'diaryloxindoles,t he development of ag eneral and robust protocol for accessing this important structural motif would be highly desirable.…”
mentioning
confidence: 99%